Islam dan Pluralisme Dalam Pembangunan Politik di Indonesia (Perspektif Pemikiran Abdurrahman Wahid) - Musda Asmara (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2017)
This paper aims to explore the thoughts of Abdurrahman Wahid about Islam and plurarism in political development in Indonesia, referring to the condition of the Indonesian nation that is difficult to live amid a climate of religious plurality, then he voiced the call for peaceful coexistence in the social life of religious communities in Indonesia. For Abdurrahman, with his keen thoughts on religion and nationalism, he directed his thoughts on inclusiveness in religious life. This paper is presented in the literature review. The results can be drawn from this paper, that the plurarism according to Gus Dur, namely the existence of awareness to know each other and dialogue sincerely so that one group with each other take and give. Islam as the majority religion in Indonesia, continued Gus Dur, has important values in creating harmony among peoples and achieve political stability in Indonesia. This idea can be glimpsed in terms of indigenous Islam, democratic values and human rights, humanitarian principles in the plurality of society, the principle of justice, egalitarian